2017
DOI: 10.1130/ges01536.1
|View full text |Cite
|
Sign up to set email alerts
|

Geodynamic implications of crustal lithologies from the southeast Mariana forearc

Abstract: The deep submergence research vehicle Shinkai 6500, diving on the Challenger segment of the Mariana forearc, encountered a superstructure of nascent arc crust atop a younger mantle with entrained fragments of metamorphosed crust. A plutonic block from this crust collected at 4900 m depth has a crystallization age of 46.1 Ma and mixed boninitic-arc tholeiitic geochemical signatures. A hornblende garnetite and two epidote amphibolites were retrieved from depths between 5938 m and 6277 m in an area dominated by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 75 publications
(84 reference statements)
2
13
0
Order By: Relevance
“…Further sampling and study will be needed to address this point. Trace element compositions of the samples we studied along with young basaltic glasses (Stern et al, 2014) and previously reported 46.1 ±0.7 Ma diorite and tonalite (Reagan et al, 2018) are shown in Figure 7 and Figure 8; fields for SEMFR basalts to the east are also shown in Figure 8. These results are broadly consistent with inferences made from major elements above.…”
Section: Geochemistrymentioning
confidence: 73%
See 4 more Smart Citations
“…Further sampling and study will be needed to address this point. Trace element compositions of the samples we studied along with young basaltic glasses (Stern et al, 2014) and previously reported 46.1 ±0.7 Ma diorite and tonalite (Reagan et al, 2018) are shown in Figure 7 and Figure 8; fields for SEMFR basalts to the east are also shown in Figure 8. These results are broadly consistent with inferences made from major elements above.…”
Section: Geochemistrymentioning
confidence: 73%
“…Comparing (a) and (e), note similar LREE depletion of 47.2 ±0.4 Ma of ol 2-pyx hornblendites and hornblende bearing basalts, suggesting these are comagmatic. Note also that both hornblendites and related basalts are more depleted than young basaltic glasses tonalite (6K-1236-R14) reported by Reagan et al (2018). Gabbros are common if not abundant components of the Mariana forearc dredged between 16 and 18 N (Bloomer, 1998).…”
Section: Alteration Around the Shinkai Seep Fieldmentioning
confidence: 80%
See 3 more Smart Citations